The Implementation of Experimental Methods in Static Fluid Topics Assisted by Genially E-Modules to Improve Learning Outcomes - Vera Evriani; Tomo Djudin; Naim Sulaiman (Jurnal Penelitian Pembelajaran Fisika, 2026)
This study aims to determine the effect of applying the experimental method assisted by an e-module developed with the Genially platform on students’ learning outcomes in static fluids. The research employed a quantitative approach with a quasi-experimental design, specifically the Nonequivalent Control Group Design. The subjects were 70 eleventh-grade students of SMA Negeri 1 Sambas in the 2024/2025 academic year, consisting of 35 students in the experimental class (XI H) and 35 students in the control class (XI F), selected using intact group sampling. The instruments included essay-based pre-test and post-test questions, as well as a validated Genially-based e-module. Data were analyzed using the Wilcoxon test, Mann-Whitney U test, and N-Gain. The results indicated a significant improvement in the experimental class with an average N-Gain of 0.64 (medium category), compared to 0.33 in the control class. The Mann-Whitney U test showed a significance value of 0.000 < 0.05, confirming a significant difference in learning outcomes between the two classes. Therefore, the use of the experimental method assisted by the Genially e-module was proven effective in enhancing students’ learning outcomes in static fluids.